(untitled) (Biocenosis, 2022)
Urban lakes exhibit severe environmental and landscape degradation as anthropogenic activities have triggered and accelerated water pollution, compromising its quality and availability, pillar of human survival. Among the most important repercussions that can be mentioned are the alteration of water quality because of point or diffuse discharges of pollutants, water erosion with consequences for increased sedimentation and eutrophication. La Sabana Lake is a specific example of how human activities degrade this artificial wetland at a landscape level. High concentrations of coliforms in the water, reflected in the physicochemical and mainly microbiological quality, make it an inappropriate space for the development of recreational activities. Strategies for the management, conservation and recovery of urban lakes based on ecological rehabilitation and bioengineering actions should be considered in order to be valued and replicated in the context of La Sabana Lake.